2021
DOI: 10.1111/avj.13094
|View full text |Cite
|
Sign up to set email alerts
|

The presence, morphology and clinical significance of vertebral body malformations in an Australian population of French Bulldogs and Pugs

Abstract: Objective To describe the incidence, morphology and clinical significance of congenital vertebral malformations (CVM) in two breeds of brachycephalic dogs presenting to a referral veterinary hospital.Design Prospective cohort study series.Materials and methods Forty-nine French Bulldogs and Pugs were prospectively evaluated and placed in one of two groups based on whether or not they presented for neurological signs referable to spinal cord disease. A computed tomography (CT) of their entire spine was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In a previous study, the presence of lumbosacral malformation was not associated with neurological signs 13 . In two studies, vertebral malformations in FB are found in clinically unaffected dogs but their populations were younger 8,11 . Nevertheless, inherent to the retrospective aspect of our study, clinical signs related to their lumbosacral endplate contour defect finding could have remained unnoticed.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In a previous study, the presence of lumbosacral malformation was not associated with neurological signs 13 . In two studies, vertebral malformations in FB are found in clinically unaffected dogs but their populations were younger 8,11 . Nevertheless, inherent to the retrospective aspect of our study, clinical signs related to their lumbosacral endplate contour defect finding could have remained unnoticed.…”
Section: Discussionmentioning
confidence: 52%
“…Vertebral abnormalities are frequently seen in spinal imaging studies of French Bulldogs (FB), mostly involving thoracic vertebrae 1–11 . Lumbosacral CT abnormalities were recently described in this breed (as well as in other brachycephalic breeds) mostly including congenital malformations such as hemivertebrae, block vertebrae, transitional vertebrae, and spina bifida with a high prevalence of 51% 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…However, short-nosed breeds are predisposed to various health issues, including short-head obstructive airway syndrome, dental problems, skin conditions, spinal malformations, brain damage, and otitis media. Additionally, they are susceptible to eye diseases such as exposure keratitis, large eyelid fissures, and eyelid entropion [51][52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%